Role of transforming growth factor-β(1) in down-regulating TNF production by alveolar macrophages during asbestos-induced pulmonary fibrosis - Lemaire, Irma (Hindawi Publishing Corporation, 1996)
Activation of alveolar macrophages (AM) for tumour necrosis factor production is suppressed initially during the inflammatory response to fibrogenic dusts. We investigated the mechanisms involved in TNF suppression, notably the role of other AM-derived mediators including prostaglandin E(2) (PGE(2)), transforming growth factor-β(1) (TGF-β(1)), and interleukin 6 (IL-6). The action of PGE(2) and TGF-β(1), on AM was different. At physiologically relevant doses (25–300 pg/ml), PGE(2) did not cause significant inhibition of Hpopolysaccharide (Lps)-induced TNF release by AM in vitro but stimulated IL-6 (up to six fold), an inhibitor of AM-derived TNT. In contrast, TGF-β(1) (0.5–50 ng/ml) inhibited both LPS-induced TNT and IL-6 release by 50% but had no effect on PGE(2) production by AM. To determine the respective contribution of these different inhibitors in TNF suppression, AM from rats exposed to fibrogenic asbestos for weeks were treated with neutralizing antibody against TGF-β(1) or indomethacin, an inhibitor of PGE(2) synthesis. Treatment of rat AM with anti-TGF-β(1) but not indomethacin, abrogated the observed TNT suppression. These results suggest that an autocrine, TGF-β(1)-dependent mechanism is involved in the down-regulation of TNF production by rat AM from animals with lung fibrosis.